Dimethylformamide Impurities as Propylene Polymerization Inhibito (2023)
This research study examined how the use of dimethylformamide (DMF) as an inhibitor af fects the propylene polymerization process when using a Ziegler–Natta catalyst. Several experiments were carried out using TiCl4/MgCl2 as a catalyst, aluminum trialkyl as a cocatalyst, and different amounts of DMF. Then, we analyzed how DMF influences other aspects of the process, such as catalyst activity, molecular weight, and the number of branches in the polymer chains obtained, using experimental and computational methods. The results revealed that as the DMF/Ti ratio increases, the catalyst activity decreases. From a concentration of 5.11 ppm of DMF, a decrease in catalyst activity was observed, ranging from 45 TM/Kg to 44 TM/Kg. When the DMF concentration was increased to 40.23 ppm, the catalyst activity decreased to 43 TM/Kg, and with 75.32 ppm, it dropped even further to 39 TM/Kg. The highest concentration of DMF evaluated, 89.92 ppm, resulted in a catalyst productivity of 36.5 TM/Kg and lost productivity of 22%. In addition, significant changes in the polymer’s melt flow index (MFI) were noted as the DMF concentration increased. When 89.92 ppm of DMF was added, the MFI loss was 75%, indicating a higher flowability of the poly mer. In this study, it was found that dimethylformamide (DMF) exhibits a strong affinity for the titanium center of a Ziegler–Natta (ZN) catalyst, with an adsorption energy (Ead) of approximately −46.157 kcal/mol, indicating a robust interaction. This affinity is significantly higher compared to propylene, which has an Ead of approximately −5.2 kcal/mol. The study also revealed that the energy gap between the highest occupied molecular orbital (HOMO) of DMF and the lowest unoccupied molecular orbital (SOMO) of the Ziegler–Natta (ZN) catalyst is energetically favorable, with a value of approximately 0.311 eV.